TECHNOLOGICAL RESEARCH OF PNEUMOSEPARATOR FOR FOREST SEED EXTRACTION (Innovation in Woodworking Industry and Engineering design, 2026)
A technological study on the operation of a pneumatic separator on a BCC Cleaner&Seed Sizer (mini) machine for extraction of Scots pine (Pinus sylvestris L.) seeds has been carried out. It is part of the new technological equipment for greenhouse production of container seed-lings in the Lokorsko forest nursery. Compared to the traditional production of saplings in Bul-garia for afforestation, the new production requires the extracted seeds to have higher quality indicators. In order to establish the optimal operating modes of the pneumoseparator for high quality seed production, with minimal seed losses in the waste in the aspiration system, a multifactor active experiment and optimization in the treatment of Scots pine seeds was conducted. The obtained results were used to establishment of a regression models to predict the techno-logical parameters and the quality of the obtained seeds depending on the operating modes of the machine. The optimal parameters for setting the pneumatic separator have been established and functional modes for Scots pine seeds extraction have been determined.